2018
DOI: 10.3126/jmmihs.v4i1.21143
|View full text |Cite
|
Sign up to set email alerts
|

Cost and generic prescription analysis of psychotropic prescriptions in psychiatric OPD of a rural tertiary care teaching hospital

Abstract: Background: There is increased interest on cost utilisation of psychotropic drugs in recent years. Objective of this study was to perform cost and generic prescription analysis of psychotropics in psychiatric outpatient department at tertiary care teaching hospital.Methods: This was cross sectional, observational and uni-centric study of 6 month duration which was performed at Psychiatric Outpatient Department at one of the tertiary care hospital, Karnataka India. Cost analysis of prescriptions containing at l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…Because of the long time of treatment and the high degree of non-compliance in psychiatry, this is particularly true (20-50 percent ) [7]. Previous studieshad suggested that women received more psychotropic medications than men [8,9]. However, no gender gaps were discovered in our research.…”
Section: Discussionmentioning
confidence: 61%
“…Because of the long time of treatment and the high degree of non-compliance in psychiatry, this is particularly true (20-50 percent ) [7]. Previous studieshad suggested that women received more psychotropic medications than men [8,9]. However, no gender gaps were discovered in our research.…”
Section: Discussionmentioning
confidence: 61%